Panch Kany?: An Evolving Civilization’s Codified Nature Worship - Mahabal, Ridhima (European Journal of Multidisciplinary Studies, 2018)
4591050243205Nature worship has been integral to most civilizations. The roots of Vedic nature worship and its mythification can be traced right from the ?gveda up-till the Itiha?sas. However the manifestation is vastly different, it is more embroiled; not through the simplistic forms of pure nature worship but through archaic human symbolism encasing it. The most evolved stage of this symbolism is through women characters famously referred to as ‘Panch Kany?’ in the oral tradition. 1352550230505Among several female characters of rich attributes and engaging story and moralistic lines that appear in the Itihasas, the following five have been singled out, encased in a ‘shlok’ and have divinity attached to them. ??????? ??????? ???? ???? ??????? ??? | ?????? ??? ????? ?????? ??????? ??????? ||The invocation of afore-mentioned five names will wash away all the sins of the invocator. This shlok is recited in 2 variants in the sub-continent. In the variant Sit?’s name is replaced by Kunti. All the five (six) women mentioned above have been heralded as women of great power and deeply enigmatic natures. However their exclusive selection may have arisen from the vital connection of their mystical feminine with the forces of nature linked to their birth. A study of their characters render an understanding that their life and choices are governed by the nature of the elements that they are born from. By looking at literary sources regarding the Panch Kany?; the purpose here is to understand the codified link between ancient nature worship and its more modern version through creation of; especially female characters; that can be easily transmitted through oral tradition and help maintain a link to the primary attempts at understanding the notion of divinity.